Social Criticism Representation in the Song Lyrics of Bingung by Iksan Skuter: Roland Barthes Semiotic Analysis - Mukminin, Muhamad Saiful; Prasetya, Kabul; Muhhit, Ahmad Abdul; Yaman, Nurinsani; Sari, Yona Tirta (UIR Press, 2024)
Social criticism in society is often presented through song lyrics. This study aims to analyze the representation of social criticism in the song Bingung by Iksan Skuter using Roland Barthes' semiotic approach. The research method employed is descriptive qualitative, with data collection techniques in the form of observation and note-taking. The primary data consist of the full transcript of the song's lyrics, while the secondary data include the relevant social, cultural, and political contexts surrounding the lyrics. The observation technique is used to comprehend the entirety of the lyrics, while the note-taking technique is employed to record and analyze the denotative, connotative, and mythical meanings that arise. The data analysis technique follows the interactive analysis model, which includes three main stages: data reduction, data presentation, and conclusion drawing. The results of the study show that the lyrics of Bingung critically reveal various social issues, such as the stigmatization of political ideologies, religious and cultural stereotypes, and the restriction of freedom of speech through narrow labels. Additionally, criticism of professions, materialism, and education highlights social injustice, while criticism of the unjust legal system reflects society's distrust of law enforcement. This study reveals that the lyrics of Bingung serve as a reflection and a medium of social criticism, encouraging the public to be more critical in understanding everyday realities. The implication of this research is that song lyrics, as a form of artistic expression, can serve effectively as a medium for social critique.